A rare case of peripartum cardiomyopathy: a multidisciplinary approach - M., Dhanya; R., Mangaiyarkarasi; K. P., Bhavani Sree; Tamilselvi, D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cardio obstetrics has emerged as an important multidisciplinary field that requires a team approach to the management of cardiovascular disease during pregnancy. Maternal heart disease complicates approximately 1% and 4% of pregnancies and accounts for up to 15% of maternal deaths. Multidisciplinary care in the antenatal period and during labour with continued surveillance extended through the puerperium along with contraceptive advise has been shown to enhance the chances of favourable outcome in these high-risk patients. Although heart disease is rare among pregnant women, it needs to be carefully managed in tertiary case sitting by a team of obstetrician. cardiologist and anaesthesiologist to obtain good maternal and fetal outcome.